Researching Transformative Technology and its Affordance for Students within Higher Music Education - Leijonhufvud, Susanna; Gullberg, Anna-Karin (Luleå tekniska universitet, Musik och dans, 2019)
Since the autumn 2018 a research project concerning Transformative Technology (TT) for the increase of wellbeing and the reduction of mental dissonance has been launched at the School of Music in Piteå. Seed money has enabled a pilot project where students within higher music education can use different types of TT. This poster will show the different types of TT used in the pilot project and some preliminary result from the user experiences. The technology in use are (i) the Heart Rate Variability (HRV) sensors and Heart Math application, (ii) the Muse headband and meditation app, (iii) the Soma Mat and Breathing Light developed at SICS and KTH, as well as the (iv) ARK-crystal developed at the Torus Tech lab. The purpose of the pilot study is to investigate how students respond to different kinds of sensors and actuators used in this TT and most importantly how the students find the technology transformable in regard to amplifying their well-being, empowering and refining their aesthetic resonance and diminishing stress and anxiety blocking them in their musical performance and development. The Equalizer